Modeling cognitive reserve in healthy middle-aged and older adults: the Tasmanian Healthy Brain Project. (23rd September 2014) - Ward, David D.; Summers, Mathew J.; Saunders, Nichole L.; Vickers, James C.
ABSTRACT: Background: Cognitive reserve (CR) is a protective factor that supports cognition by increasing the resilience of an individual's cognitive function to the deleterious effects of cerebral lesions. A single environmental proxy indicator is often used to estimate CR (e.g. education), possibly resulting in a loss of the accuracy and predictive power of the investigation. Furthermore, while estimates of an individual's prior CR can be made, no operational measure exists to estimate dynamic change in CR resulting from exposure to new life experiences. Methods: We aimed to develop two latent measures of CR through factor analysis: prior and current, in a sample of 467 healthy older adults. Results: The prior CR measure combined proxy measures traditionally associated with CR, while the current CR measure combined variables that had the potential to reflect dynamic change in CR due to new life experiences. Our main finding was that the analyses uncovered latent variables in hypothesized prior and current models of CR. Conclusions: The prior CR model supports multivariate estimation of pre-existing CR and may be applied to more accurately estimate CR in the absence of neuropathological data. The current CR model may be applied to evaluate and explore the potential benefits of CR-based interventions prior to dementia onset.